Modelo de nicho ecológico para predecir la distribución potencial de Antracnosis (Colletotrichum acutatum) en el cultivo de chocho (Lupinus mutabilis Sweet) en Ecuador, periodo 2019- 2020. - Quishpe Defaz, Nila Thalía (2020)
The research was carried out with the objective of developing ecological niche models to predict the potential distribution of anthracnose (Colletotrichum acutatum) in Ecuador. This study focused on the affectation of this pathogen in the cultivation of lupine (Lupinus mutabilis Sweet) that is cultivated in the Ecuadorian Sierra region. A database of previous samplings in agroecological areas where this legume is produced was obtained, in addition we worked with bioclimatic variables downloaded from WorldClim; Through Pearson's correlation analysis, those that influence the development habitat of this pathogen were determined. The information obtained was processed in MaxEnt, a maximum entropy program that through algorithms makes potential distribution maps, it was analyzed under two types of spatial models, MIROC5 and HadGEM2-ES under Representative Concentration Trajectories (RCP) 2.6 and 8.5 for the years 2050 and 2080. Once the models were obtained, a description was made that is compared with the current and future potential distribution model where the area of the curve is considered good from 0.75 to 1. Interpreting a good precision in the MIROC5 global circulation models, it was determined that for the year 2080 of scenario RCP 8.5 there is a probability of 5.45% with an estimated area of 3,272,066 km2 of developing anthracnose (Colletotrichum acutatum) in the cultivation of lupine (Lupinus mutabilis Sweet). Determining that the provinces with high and very high probability of developing the pathogen will be in the provinces of Cotopaxi, Bolívar, Tungurahua and Chimborazo, in which controls must be carried out to minimize the impact on crops avoiding economic losses to farmers.